2021
DOI: 10.3390/plants10010119
|View full text |Cite
|
Sign up to set email alerts
|

Sterols and Triterpenes from Dobera glabra Growing in Saudi Arabia and Their Cytotoxic Activity

Abstract: A new lupane caffeoyl ester, lup-20(29)-ene 3β-caffeate-30-al (7), and a new oleanane-type triterpene, 3β-hydroxyolean-13(18)-en-12-one (17), were isolated from the aerial parts of Dobera glabra (Forssk), along with ten known triterpenes, including seven lupane-type lupeol (1), 30-nor-lup-3β-ol-20-one (2), ∆1-lupenone (3), lup-20(29)-en-3β,30-diol (4), lupeol caffeate (5), 30-hydroxy lup-20(29)-ene 3β-caffeate (6), and betunaldehyde (8); three oleanane-type compounds were also identified, comprising δ-amyrone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Through GC-MS, the contents abundant in N. mirandaleaf-acetone were detected and identified (Table 3). We found that the top four contents, plumbagin (28.52%) [57][58][59][60], lupenone (11.45%) [69][70][71], palmitic acid (5.49%) [72][73][74], and stigmast-5-en-3-ol (5.06%) [75], especially plumbagin and lupenone, are anticancer compounds. This might be why N. miranda-leaf-acetone possesses strong cytotoxic activities.…”
Section: Discussionmentioning
confidence: 92%
“…Through GC-MS, the contents abundant in N. mirandaleaf-acetone were detected and identified (Table 3). We found that the top four contents, plumbagin (28.52%) [57][58][59][60], lupenone (11.45%) [69][70][71], palmitic acid (5.49%) [72][73][74], and stigmast-5-en-3-ol (5.06%) [75], especially plumbagin and lupenone, are anticancer compounds. This might be why N. miranda-leaf-acetone possesses strong cytotoxic activities.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies also showed that sterols possess cytotoxicity activity against colorectal cancer (HCT-116), hepatocellular carcinoma (HepG-2), and prostate cancer (PC-3) cell lines (Abdel-Mageed et al, 2021). Both sinaphyl alcohol acetate and sinaphyl alcohol diacetate belong to the phenylpropanoid compound.…”
Section: Mm-pbsa Calculationmentioning
confidence: 96%